Dry Retting of Jute under Limited Aqueous System Vs Water Based Conventional Retting of Jute: A Comparative Study. Issue 15 (23rd November 2022) - Chakrabarti, Syamal Kanti; Saha, Sakshi Gopal; Roy, Ipsita; Deka, Amal Chandra; Bose, Sandip; Chakraborty, Ritwik; De, Samar; Dewan, Atiar Rahaman; Paral, Rajkumar; Paul, Palash; Sanyal, Partha; Mukhopadhyay, Gopal; et al.
ABSTRACT: Jute plant retting is a preferential rotting process in which jute plants are submerged in water and subsequently jute fibers are extracted out by decomposing the cellular tissues and pectin surrounding the fiber bundles through the joint action of water and aquatic/soil microorganisms. Due to the shortage of water during retting period of jute, all crops cannot be stacked at a time and therefore farmers are often compelled to harvest over-matured plants and use the same water body repeatedly for retting. This generates inferior quality of fiber. Traditional retting is also labor intensive and not environment friendly and takes longer time to ret. A feasibility study has been undertaken for dry retting of jute plants on land under water limiting condition using a defined microbial consortium. Field trials of dry retting of jute plants carried out at farmer's level have shown promising results wherein jute plant retting can be achieved in shorter time without submerging jute plants in water body. Quality of jute fibers obtained from such dry retting process is comparable to the conventionally retted jute process.